Autophagy activation by rapamycin reduces severity of experimental osteoarthritis. Issue 4 (14th November 2011) - Caramés, Beatriz; Hasegawa, Akihiko; Taniguchi, Noboru; Miyaki, Shigeru; Blanco, Francisco J; Lotz, Martin
Abstract : Objectives: Osteoarthritis is associated with cell death and extracellular matrix degradation in articular cartilage. Autophagy is an essential cellular homeostasis mechanism that was found to be deficient in ageing and osteoarthritic cartilage. This study determined whether pharmacological inhibition of the mammalian target of rapamycin (mTOR), a key inhibitor of autophagy, has disease-modifying activity in experimental osteoarthritis. Methods: Experimental osteoarthritis was induced by transection of the medial meniscotibial ligament and the medial collateral ligament in 2-month-old C57Bl/6 mice (n=36). Rapamycin (1 mg/kg weight/day) (n=18 mice) or dimethyl sulphoxide vehicle control (n=18 mice) was administered intraperitoneally for 10 weeks. Histopathological changes in articular cartilage and synovium were examined by using semiquantitative scoring systems. Rapamycin effects on mTOR signalling, autophagy, cartilage homeostasis and inflammation were analysed by immunohistochemistry and immunofluorescence staining. Results: Rapamycin affected the mTOR signalling pathway in mouse knee joints as indicated by the inhibition of ribosomal protein S6 phosphorylation, a target of mTOR and activation of LC3, a main marker of autophagy. The severity of cartilage degradation was significantly (p<0.01) reduced in the rapamycin-treated group compared with the control group and this was associated with a significant (p<0.05) decrease in synovitis. Rapamycin treatment also maintained cartilage cellularity and decreased ADAMTS-5 and interleukin-1β expression in articular cartilage. Conclusions: These results suggest that rapamycin, at least in part by autophagy activation, reduces the severity of experimental osteoarthritis. Pharmacological activation of autophagy may be an effective therapeutic approach for osteoarthritis.